Levosimendan: new indications and evidence for reduction in perioperative mortality?. Issue 4 (August 2016) - Pisano, Antonio; Monti, Giacomo; Landoni, Giovanni
Abstract : Purpose of review: In the last years, the perioperative use of levosimendan in cardiac surgery patients is spreading. Moreover, newer indications have been suggested such as the treatment of sepsis-associated myocardial dysfunction. In the present review, we discuss the most recent evidences in these settings. Recent findings: Levosimendan has been seemingly confirmed to reduce mortality in patients undergoing cardiac surgery. In particular, it appears to be the only inotropic drug to have a favorable effect on survival in any clinical setting. Moreover, levosimendan has been shown to exert a cardioprotective action and to reduce acute kidney injury, renal replacement therapy, and ICU stay in cardiac surgery patients. Finally, levosimendan has been suggested to reduce mortality in patients with severe sepsis and to improve renal outcomes in critically ill patients. Summary: Although a strong rationale likely exists to use levosimendan in the setting of perioperative and critical care medicine, evidence mainly comes from small and often poor-quality randomized clinical trials, whose results acquire significance only when pooled in meta-analyses. Moreover, some aspects related to which subgroups of patients may derive the most benefits from receiving levosimendan, to the optimal timing of administration, and to the potential adverse effects need to be further clarified. Important insights will be hopefully provided soon by the several large multicenter investigations which are currently ongoing.